M2M management platform - Faria, Bruno Miguel Cunha (2015)
The Internet of Things is still a fast growing area and topic of interest. New solutions and implementations keep emerging, both in service oriented solutions or device oriented solutions with M2M communications, therefore promoting the creation of new business models. Thus, as a natural evolution, came the possibility to abstract sensor management from service creation. Allowing a delegation of sensor management from the sensor providers, to focus on content creation through services. However, this delegation brings new concerns regarding access control. Consequently, this dissertation proposes a possible solution to this problem, enclosed in a service oriented platform interconnected with an ETSI M2M solution. Promoting interoperability between sensors and allowing a great elasticity in service creation.